Mangrove Ecosystem Degradation through Land Conversion in Indonesia’s Coastal Areas: A Review - Apriani Apriani; Delistiani (Journal of Epidemiology and Health Science, 2025)
Background: Mangrove forests are unique plant formations commonly found in protected coastal areas in tropical and subtropical regions. The existence of mangrove forests is essential due to their ecological, economic, and social benefits. Mangroves play a significant role in carbon sequestration, preventing seawater intrusion, reducing erosion and coastal abrasion, acting as natural wave barriers, filtering water, and serving as nursery grounds for various marine species, particularly fish. Objective: This study aims to analyze the factors driving mangrove land conversion in Indonesia's coastal areas and to examine its environmental and socio-economic impacts. Methods: This research employs a literature review approach. Relevant articles were sourced from the PubMed and Google Scholar databases using the keyword "mangrove land conversion in Indonesia." The selected studies were analyzed to identify the patterns and consequences of mangrove land conversion. Results: The findings indicate that mangrove land conversion in Indonesia’s coastal areas is driven by various factors, including the development of aquaculture (such as fish and shrimp ponds), the establishment of rice fields, settlements, office buildings, plantations, industrial areas, and other agricultural activities. The increasing demand for palm oil has also led to large-scale land clearing. Additionally, population growth in coastal areas contributes to the expansion of infrastructure such as roads and ports, which often involves the clearing of mangrove forests. Environmental degradation resulting from this conversion includes coastal abrasion and the overexploitation of mangroves for charcoal production, firewood, and construction materials. These activities lead to deforestation and the degradation of mangrove ecosystems. Conclusion: Mangrove land conversion in Indonesia is influenced by a combination of economic, social, and environmental factors. The low-income levels of coastal communities often push them towards activities that lead to land-use changes, while government policies may both limit and, in some cases, indirectly encourage deforestation. Furthermore, natural factors such as nutrient depletion, substrate alteration, salinity changes, and high wave exposure contribute to the inability of certain mangrove species to regenerate, exacerbating ecosystem degradation. Keywords: Natural Resource Conservation, Mangrove Land Conversion, Social and Economic Factors, Coastal Ecosystems, Indonesia.